A law for nanotechnology in Malaysia / Nur Hafidah Abdul Kadir, Farah Wahida Zolkhifly and Nurjannah Mohamed Noordin. - Abdul Kadir, Nur Hafidah; Zolkhifly, Farah Wahida; Mohamed Noordin, Nurjannah (Faculty of Law, 2008)
"A Law for Nanotechnology" is the title for this project paper. This project paper is about nanotechnology, where at the first place we were discussing on that there is a need for us to have law on nanotechnology. This is because; nanotechnology development can be seen everywhere and it can be said that there are high potential risks of nanotechnology that might affect human and the environment. In order to prove this statement, we have discussing on what nanotechnology is all about at the second chapter of this project paper. Then, we also look into the development of nanotechnology in foreign countries such as the United States of America and the United Kingdom. We also discussed on the development of nanotechnology in Malaysia itself on how far Malaysia has developed in this new technology. In addition, in chapter three, we have focused on the usage and the adverse effects of nanotechnology. In this chapter, we have laid down examples of products, which can bring benefits as well as examples of products, which can give harm to the people and environment. It can be said that though nanotechnology does give benefits, but there are still the possible adverse effects when people used this technology. So, in chapter four, we have analysing the available Malaysian laws, which may be applied to deal with the potential adverse effects of nanotechnology. We have also made our references to the foreign laws such as the laws in the United States of America and the laws in the Switzerland, which we think can be used as a guideline if we wanted to enact law on Nan technology. In conclusion, we agreed that the available Malaysian laws are not sufficient to deal with the Nan technology. Therefore under chapter five, we have given several recommendations on what should be included in the law of nanotechnology.